An Empirical Study on Challenging Math Problem Solving with GPT-4 - Wu, Yiran; Jia, Feiran; Zhang, Shaokun; Li, Hangyu; Zhu, Erkang (Eric); Wang, Yue; Lee, Yin Tat; Peng, Richard; Wu, Qingyun; Wang, Chi (arXiv, 2023)
Employing Large Language Models (LLMs) to address mathematical problems is an intriguing research endeavor, considering the abundance of math problems expressed in natural language across numerous science and engineering fields. While several prior works have investigated solving elementary mathematics using LLMs, this work explores the frontier of using GPT-4 for solving more complex and challenging math problems. We evaluate various ways of using GPT-4. Some of them are adapted from existing work, and one is MathChat, a conversational problem-solving framework newly proposed in this work. We perform the evaluation on difficult high school competition problems from the MATH dataset, which shows the advantage of the proposed conversational approach.